The extra virgin olive oil handbook - Peri, C. (Claudio) (John Wiley & Sons, 2014)
According to European legislation, extra virgin is the top grade of olive oils. It has a superior level of health properties and flavour compared to virgin and refined olive oils. Mediterranean countries still produce more than 85% of olive oil globally, but the constant increase of demand for extra virgin olive oil has led to new cultivation and production in other areas of the world, including California, Australia, China, South Africa and South America. At the same time, olive oil's sensory properties and health benefits are increasingly attracting the attention and interest of nutrition.